Primeira ocorrência da ordem Caloneurodea no Carbonífero de Portugal: Lusitaneura covensis nov. gen., nov. sp. - J.P. Loureiro (2010)
Lusitaneura covensis gen. nov., sp. nov. The authors present the description of the first Portuguese representative of the Palaeozoic insect order Caloneurodea from the Carboniferous of the Douro Basin (NW of Portugal)